2019
DOI: 10.1038/s41467-019-12592-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive MoS2 photodetector by serial nano-bridge multi-heterojunction

Abstract: The recent reports of various photodetectors based on molybdenum disulfide (MoS2) field effect transistors showed that it was difficult to obtain optoelectronic performances in the broad detection range [visible–infrared (IR)] applicable to various fields. Here, by forming a mono-/multi-layer nano-bridge multi-heterojunction structure (more than > 300 junctions with 25 nm intervals) through the selective layer control of multi-layer MoS2, a photodetector with ultrasensitive optoelectronic performances in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…The role of conguration of device heterojunctions has been emphasized for developing high performance MoS 2 photodetectors. Kim et al 348 reported MoS 2 photodetectors using serial nano-bridge multi-heterojunctions. The MoS 2 photodetectors based on laser irradiation were assigned as type (1) monolayer, type (2) multilayer, type (3) parallel heterojunction, type (4) serial heterojunction, type (5) parallel nanobridge multi-heterojunction, and type (6) serial nano-bridge multi-heterojunction.…”
Section: Conguration Of Mos 2 Heterojunctionsmentioning
confidence: 99%
“…The role of conguration of device heterojunctions has been emphasized for developing high performance MoS 2 photodetectors. Kim et al 348 reported MoS 2 photodetectors using serial nano-bridge multi-heterojunctions. The MoS 2 photodetectors based on laser irradiation were assigned as type (1) monolayer, type (2) multilayer, type (3) parallel heterojunction, type (4) serial heterojunction, type (5) parallel nanobridge multi-heterojunction, and type (6) serial nano-bridge multi-heterojunction.…”
Section: Conguration Of Mos 2 Heterojunctionsmentioning
confidence: 99%
“…In the past 30 years, considerable efforts have been successfully devoted to best detect single photons emitted by discrete sub-wavelength size objects such as single molecules, or to localize such point-like emitters when sparsely distributed over an object field. This has led to a huge diversity of methods aimed at single photon detection and imaging [1][2][3][4][5] .…”
Section: Detectivity Optimization To Detect Of Ultraweak Light Fluxesmentioning
confidence: 99%
“…Bandgap tuning for nanomaterials will significantly improve the on/off current ratio, photoresponsivity, quantum efficiency, conductivity and others. Layer-by-layer etching for multilayer materials by low-energy plasma technology (double mesh grids inserted for plasma apparatus such as chlorineradical ICP, neutral-beam ICP and ion beam ICP) with no physical damage would be the next research direction and can be applied to the other low-dimensional materials [28,43] to achieve ultrahigh performance of electronic and optoelectronic devices [28,43]. For instance, in the latest report in 2019, Kim et al utilized a chlorine ICP innovative plasma apparatus that has no physical damage effect by inserting double mesh grids for cyclic ALE process on intrinsic multilayer MoS 2 and successfully fabricated heterostructured photodetector with ultra-responsivity (~10 6 A/W) in the visible range [43].…”
Section: Discussionmentioning
confidence: 99%